The Archaeology of the Aru Islands, Eastern Indonesia - O'Connor, Sue; Spriggs, Matthew; Veth, Peter (Terra Australis, 2006)
This volume describes the results of the first archaeological survey and excavations carried out in the fascinating and remote Aru Islands, Eastern Indonesia between 1995 and 1997. The naturalist Alfred Russel Wallace, who stopped here in search of the Birds of Paradise on his voyage through the Indo-Malay Archipelago in the 1850s, was the first to draw attention to the group. The results reveal a complex and fascinating history covering the last 30,000 years from its early settlement by hunter-gatherers, the late Holocene arrival of ceramic producing agriculturalists, later associations with the Bird of Paradise trade and the colonial expansion of the Dutch trading empires. The excavations and finds from two large Pleistocene caves, Liang Lemdubu and Nabulei Lisa, are reported in detail documenting the changing environmental and cultural history of the islands from when they were connected to Greater Australia and used by hunter/gatherers to their formation as islands and use by agriculturalists. The results of the excavation of the late Neolithic - Metal Age midden at Wangil are discussed, as is the mysterious pre-Colonial fort at Ujir and the 350-year old ruins of forts and a church associated with the Dutch garrisons.